Trudeau’s blackface apology rings hollow and highlights anti-Arab stereotypes - Bahdi, Reem (The Conversation, 2019)
Justin Trudeau’s use of blackface and Arab costumes has raised questions about his authenticity on diversity issues. It also highlights the ongoing discrimination faced by Arab and Muslim Canadians.
Keywords: Reem Bahdi